The role of data and information exchanges in transport system disaster recovery: A New Zealand case study. (October 2019) - Blake, D.M.; Stevenson, J.; Wotherspoon, L.; Ivory, V.; Trotter, M.
Abstract: The Mw 7.8 earthquake on 14 November 2016 near Kaikōura, New Zealand had major impacts on the country's transport system. Road, rail and port infrastructure was damaged, creating substantial disruption for transport operators, residents, tourists, and business owners across several regions. During the response and recovery phases, a large amount of information and data associated with the transport system was generated, managed, analysed, and exchanged within and between organisations to assist decision making. In this paper, we characterise how the transport system, infrastructure, and supply chain responded and adapted to earthquake-related disruptions and examine the flow and use of information in post-disaster (response and recovery) decision making across all transport modes. We present key findings from a post-earthquake assessment with the aim of improving information and data exchanges and related decision making in the transport sector during future events. This research commenced a year after the earthquake and involved 35 different stakeholder groups. Many information exchanges were effective, enabling the transport system to respond and adapt successfully, and allowing the continued mobility of users and goods. Organisations responding to transport disruptions drew on existing data sources in new ways, collected novel datasets, and leveraged relationships to manage information exchanges. There is, however, scope for improvement to reduce barriers to information exchanges and enhance post-disruption data usage between the numerous organisations involved in transport recovery. This may include improved clarity on organisational boundaries and an enhanced role for coordinators to act as single points of contact for transport sectors.